Dietary Antioxidants and Prevention of Non-Communicable Diseases - Giuseppe Grosso (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Numerous epidemiological studies have demonstrated the association between oxidative stress and non-communicable disease, including cardiovascular disorders, mental disease, and several types of cancer. Oxidative stress is commonly known as an imbalance in the production of reactive oxygen species (ROS) and the biological antioxidant defense system. Exogenous antioxidants have gained great attention because of their beneficial role in preventing chronic disease. A balanced diet contains hundreds of naturally occurring antioxidant compounds, including polyphenols and vitamins. Antioxidants are commonly found in vegetables, fruits, cocoa, grain cereals, olive oil, nuts and beverages, such as coffee and tea. This book presents original research and reviews of literature concerning dietary antioxidants and human health.